Current status and improvement strategies of Chinese contemporary design: a visualisation research based on CiteSpace - Yang, Fang; Ismail, Issarezal; Abdul Hadi, Hamidi; Wu, Yuxuan (Universiti Teknologi MARA, Perak, 2025)
The development of design relates to many areas of the country's economy and people's lives. To understand the current research of modern design in China and analyse future development trends, the published paper about China modern design in Web of Science Core Collection (WOSCC) database and China National Knowledge Infrastructure (CNKI) were investigate by visualised analysis use CiteSpace software. The following aspects between international work and Chinese work are compared in the present study, including publication quantity, national collaboration network, disciplinary type network, author analysis, and evolution of hotspots. The results show that the number of international literatures on Chinese modern design exceeds that of in China and with an increasing trend both. Although the nations collaborations in CNKI is inferior to that of in WOSCC, China is the most influential compared with other countries, which indict many studies are published in non-Chinese journals, result a truth that it is not conducive to the dissemination of design research between scholars and Chinese designers. For disciplinary distribution and core author, the international research teams are more diverse and widespread, while domestic networks are relatively concentrated with significant differences in research focuses. Chinese design researcher needs to strengthen communication and cooperation between different disciplines either domestic or international, which is an effective means for the advancement of design in international researchers. As for research hotspots and trends, international researchers focus on the development directions of design with digitalisation, intelligence, and virtualization, while domestic researchers continue to research the historical roots of traditional Chinese culture and reflect on the integration relationship between traditional culture and design. Based on the analyses above mentioned, some suggestions are present for improve the design philosophy and methodology, and ultimate enhance the competitiveness of Chinese design.